Rukhsah bagi Penderita Depresi Mayor dalam Perspektif Fikih Ibadah - Munira Munira; Sri Ujiana Putri; Nidaul Haq (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
Major depression is one of the serious psychological problems and can affect a person's quality of life significantly and can hinder individuals from carrying out worship optimally. This study aims to analyze the concept of rukhsah and its implications for people with major depression in the perspective of religious jurisprudence. This research is library research using normative and philosophical approach methods. The results showed that in the perspective of religious jurisprudence, people with major depression get rukhsah to carry out worship according to their conditions. In addition, this study also found several examples of rukhsah in worship such as the loss of worship obligations, replacing worship with lighter ones and getting help from others in carrying out worship. This research makes an important contribution in understanding the concept of rukhsah in religious jurisprudence for people with major depression. These findings can be used as a guideline for people with major depression and religious practitioners in facing challenges in carrying out worship. It is hoped that this research can increase public understanding and awareness and provide practical solutions in fulfilling worship obligations for people with major depression.